Effects of exogenous and endogenous cues on attentional orienting in deaf adults - Li, Yunsong; Luo, Meili; Zhang, Xilin; Wang, Suiping (Frontiers in Psychology, 2022)
Adults who are deaf have been shown to have better visual attentional orienting than those with typical hearing, especially when the target is located in the periphery of the visual field. However, most studies in this population have assessed exogenous visual attention orienting (bottom-up processing of external cues) rather than endogenous visual attention orienting (top-down processing of internal cues). We used a target detection task to assess both types of visual attention orienting. A modified cue-target paradigm was adopted to assess facilitation effects of exogenous and endogenous cues during short and long interstimulus intervals (ISI), using a 2 (Group: deaf/typically hearing) * 2 (Location: central/peripheral) * 2 (Cue Type: exogenous/endogenous) mixed factorial design. ANOVAs showed that both exogenous cues and endogenous cues can facilitate deaf adults’ visual attentional orienting, and the facilitation effect of exogenous cues on attention orienting was significantly stronger for deaf participants than hearing participants. When the ISI was long, the effect was significantly stronger when the exogenous cue appeared in the periphery of the visual field. In the periphery, deaf adults benefited most from exogenous cues, whereas hearing adults benefited most from endogenous cues. The results suggest that not only exogenous cues but also endogenous cues can facilitate deaf adults' visual attentional orienting. However, the effect of exogenous cues appears to be greater, especially when the stimulus appears in the peripheral visual field.